Federal Deep Learning Approach of Intrusion Detection System for In-Vehicle Communication Network Security - In-Seop Na; Anandakumar Haldorai; Nithesh Naik (IEEE Access)
In order to stay current with technology, in-vehicle communication has been enhanced daily. Control area network (CAN) is widely adopted due to the exceptional efficiency and reliability. CAN is susceptible to various network-level attacks due to the shortfall in security protocols. This article presents a new approach in addressing this challenge by introducing a unique intrusion detection system. It utilizes a federal learning framework which employs Convolutional Neural Networks as well as Long-Term Short Memory. The goal of this hybrid methodology is to improve intrusion detection efficacy within the framework of federal learning for IoT while overcoming the drawbacks of current techniques. This approach is commonly employed for spatial extraction of features, permitted the model to detect patterns that may indicate possible attacks. Additionally, it is capable of arresting temporal dependencies over time in the information. This work implements a zero-trust security approach for storing information in local device edges and only sharing the weights that were learned with the centralised federal network. This network collects information from different sources for enhancing the correctness of the universal learning approach. Experimental results show that the proposed technique can effectively detect attacks in real-time on the bus, with a much higher detection ratio. Based on the analysis, it can be discovered that the HCRL SA dataset, when used with the proposed hybrid model, with an impressive accuracy rate, and precision of 99.94% and 99.86% respectively. It is also found that the recall and area of the curve perform better by implementing the proposed technique. It is recorded to be 99.10% and 99.21% respectively.